Oral and Maxillofacial Surgery - Sridharan, Gokul; Sridharan, Gokul (IntechOpen, 2021)
Oral and maxillofacial surgery is a specialized branch of dentistry that deals with the surgical management of various head and neck pathologies. The specialty focuses on reconstructive surgery of the oro-facial region, surgery of facial trauma, the oral cavity and jaws, dental implants as well as cosmetic surgery. As such, surgeons in this field require extensive knowledge of not only these various surgical procedures but also head and neck anatomy. This book provides comprehensive information on both. Its goal is to educate oral and maxillofacial surgeons to enable them to treat a wide range of conditions and diseases using the most current surgical trends.
English
Keywords: Dentistry; Oral & maxillofacial surgery